Eye health related policies, strategies and program of Nepal: a policy research. - Sah,Dipak Kumar (2020)
ABSTRACT: Eye health system in Nepal is governed mainly by philanthropic social organizations with the history of service dating back to more than three decades. However, the national policies addressing the six building blocks of eye health system is scarcely available and the organizations are running the services on their own. So this study aims to find out existing gaps in national policies, strategies, and program in eye health of Nepal and recommend the way forward. This policy research has been conducted through the process of scoping review including the standard six steps. A total of 82 documents comprising policy documents, research articles, annual reports of eye health facilities and organizations, global documents on commitments and targets have been reviewed. All the documents were entered into data charting form and the information regarding the six building blocks of eye health system was collated and summarized. Furthermore, stakeholders in eye health of Nepal were consulted. Eye health services in Nepal has not been integrated into government health system although stated in National health policy 2076. Among the three main cadres of eye health human resource, the number of optometrist and ophthalmic assistant has exceeded the WHO south East Asia target while, more than 200 ophthalmologists are still required. There is no clear demarcation of their work and there are no any policy documents for addressing this and their placement. Policy has been there to regulate medicine but it is silent in regulating spectacle and other ocular devices. There is no system of consolidating data from eye health facilities into province level or national level and are not reflected in National Health Information Management System. The government fund has least share in financing eye health covering only about five percent. The roles and responsibilities of governing body has not been well documented. Eye health care system is not adequately addressed by policies, strategies, and programs in Nepal. Moreover, proper implementation of existing policies and plans is required. Expansion of health insurance can be effective way of financing eye health. Monitoring mechanism of eye health information and supplies like spectacles and ocular devices should be developed and executed.